Shear strengthening of pre-cracked and non pre cracked reinforced concrete continuous beams using bi directional CFRP strips - Ali, Noorwirdawati (2014)
Shear failure of a reinforced concrete beam is catastrophic where it occurs suddenly and without any warning. The use of FRP sheet as a strengthening and repairing material is an effective method to enhance the shear capacity of the beam. Extensive researches have been conducted on the shear strengthening of reinforced concrete simply supported beams using FRP composites. However, strengthening continuous beams in shear have received very little attention among the researchers although most of the existing structures are in the form of continuous condition. Furthermore, there are restraints to add shear reinforcement to the existing reinforced concrete beams when beams are part of the floor-beam system. In the design guideline by ACI 440 Committee mentioned that the existing theoretical model have not been confirmed to be use for strengthening in negative moment region which existed in continuous beam. Therefore, in order to address the problem, a study on shear strengthening of reinforced concrete continuous beam using CFRP strips was conducted. An experimental work on 14 full-scale reinforced concrete continuous beams with a size of 150x350x5800mm was carried out. Simulation using finite element software ATENA v4 and theoretical analysis was also conducted. The variables involved a number of CFRP strips layers (one and two layers), wrapping schemes (four sides and three sides), orientation of CFRP strips (0/90 and 45/135 degree) and shear span to effective depth ratio, av/d (2.5 and 3.5). The type of FRP used was bi-directional CFRP strips. Two beams were un-strengthened and treated as the control specimens whilst the other 12 beam were wrapped with CFRP strips. From the experimental results, all beams failed in shear as expected. Beams wrapped with CFRP strips recorded shear capacity enhancement of around 10.12% to 53.74% compared to the control specimens. Beam wrapped with two layers of CFRP strips at four sides of the beam recorded the highest shear enhancement. Simulation study also showed similar behaviour in terms of shear capacity and crack patterns. Three existing theoretical models; ACI 440, Khalifa and Nanni and fib models were adopted for theoretical comparison of shear capacity contributed by CFRP, Vf while for shear capacity contributed by concrete, Vc and stirrups, Vs, the equation from ACI 318-08, BS8110 and EC2 was adopted. The ACI 440 model had shown the closer value with the experimental results and a modified ACI 440 model was proposed on the effective strain limit and bond-reduction coefficient.